Diet change and exercise enhance protein expression of CREB, CRTC 2 and lipolitic enzymes in adipocytes of obese mice. Issue 1 (December 2016) - Woo, Jinhee; Kang, Sunghwun
Abstract Background The study investigated the effects of regular exercise and diet changes on the change in metabolic processes of the cAMP-Response Element-Binding Protein-Regulated Transcription Coactivator (CRTC) family and its sub-lipolysis. Methods Four-week-old C57/black male mice received an 8-week diet of general formula (control, CO;n  = 10) or a high fat diet (HF;n  = 30) to induce obesity. Thereafter, the mice received another 8-week regimen of general formula CO (n  = 10) diet, continuous HF diet (n  = 10), switched to general formula (diet change, DC;n  = 10) or switched to general formula + exercise (diet and exercise, DE;n  = 10). Results The DE group displayed significantly lower body weight, abdominal fat and lipid profiles (p  < 0.05). The DE group also displayed significantly lower (35 %) CRTC 2 activity than the CO (p  < 0.05). Activities of adipose triglyceride lipase (ATGL), hormone sensitive lipolitic enzyme (HSL) and monoacylglycerol lipase (MGL) were significantly higher (51 %, 38 %, 49 %) in the DE group than the HF group (p  < 0.05). MGL, there were no differences between the CO group, HF group, and DC group, with the DE group (70 %) being significantly higher (p  < 0.05). Conclusion Change in diet in the absence of exercise was not associated with changes in adipose tissue CRTC family lipase activity, indicating that lipolysis metabolic processes are effective only when diet and exercise are carried out together.